PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA RITATOON PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 27 PASAR KAMBANG KABUPATEN PESISIR SELATAN - Chandra, Figo Pratama; ladiva, Hasmai bungsu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of students in learning IPAS which is caused because the teacher has not used the learning model and the students' understanding is not optimal for the learning material provided. this study aims to improve the learning outcomes of students in learning IPAS using the Problem-based Learning model assisted by ritatoon media in class IV of SD Negeri 27 Pasar Kambang, South Coastal Regency. This research is a class action research (PTK) using Qualitative and Quantitative approaches, which were carried out in two cycles. The subjects of this study were teachers and fourth grade students of SD Negeri 27 Pasar Kambang with a total of 23 students. The results showed an increase in: a) Teaching Module in cycle I obtained an average of 83.93% (B), increased in cycle II obtained an average of 96.43% (SB), b) teacher activity in cycle I obtained an average of 81.26% (B), increased in cycle II obtained an average of 93.75% (SB), while the aspect of students in cycle I obtained an average of 76.57% (C), increased in cycle II with an average of 87.50% (B), c) student learning outcomes in cycle I obtained an average of 68.81% (K) and increased in cycle II with an average of 85.15% (B), it can be concluded that the Problem Based Learning model assisted by Ritatoon Media can improve IPAS learning outcomes in class IV.